2015
DOI: 10.1515/jpem-2014-0533
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in obese children and adolescents in Serbia: prevalence and risk factors

Abstract: High prevalence of MS emphasizes the need for prevention and treatment of childhood obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…A history of a cardiovascular disease, diabetes, obesity, and hypertension in the family was present in a significant number of children in this study. This might have added to the increased prevalence of MS in the study population as shown in previous studies (14,18,25). Insulin resistance was more common in children with MS.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…A history of a cardiovascular disease, diabetes, obesity, and hypertension in the family was present in a significant number of children in this study. This might have added to the increased prevalence of MS in the study population as shown in previous studies (14,18,25). Insulin resistance was more common in children with MS.…”
Section: Discussionmentioning
confidence: 74%
“…There have been various studies published worldwide on the prevalence of MS in children and adolescents (10, [14][15][16][17][18][19][20][21][22][23][24][25]. These are mainly hospital-based studies, with few being conducted in school or community settings (10, 16,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Methodology used was similar to our previous research of metabolic comorbidities in the obese youth [ 21 , 22 ]. BMI percentiles and standard deviation scores (SDS) were calculated in accordance with WHO growth reference charts using WHO Anthro and AnthroPlus software and waist circumference percentiles (WC) according to the reference values by Fernandez et.…”
Section: Methodsmentioning
confidence: 99%
“…There is a wide opinion that the rising prevalence of obesity is connected with the growing number of early complications in children and adolescents, such as type 2 diabetes mellitus (T2D) and metabolic syndrome (MS) [ 1 , 10 , 11 ]. MS is defined as a cluster of cardiovascular risk factors: impaired glucose tolerance, dyslipidemia (elevated triglycerides and low high-density lipoprotein cholesterol (HDL)), hypertension, and abdominal obesity [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The International Diabetes Federation (IDF) in 2007 issued a unifying definition of MS in children and adolescents, and this progress enabled the comparison of different studies in the future [ 20 ]. Many studies are published on the prevalence and impact of the MS in the adult population, but there is limited information on the epidemiology of MS in children and adolescents, especially in Eastern Europe and the Mediterranean area [ 10 , 17 ].…”
Section: Introductionmentioning
confidence: 99%